Meningkatkan Kemampuan Melakukan Operasi Hitung Pecahan Pelajaran Matematika Melalui Pembelajaran Kooperatif Teknik Permainan Kartu Bagi Siswa Kelas V Mi Maarif NU Nurul Ulum Bulurejo Benjeng - nur hudah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
ABSTRACT Based on the author's experience in the field, many failures in the mathematics learning process faced by all students. Students feel bored, lazy and boring when faced with learning mathematics. To deal with such problems, the efforts made by the teacher are to arouse student learning motivation. Some things that can be done by the teacher so that learning mathematics becomes fun is to try various models and techniques in learning. One of the learning models used is cooperative learning of card game techniques. The problem examined in this study is how is the effort to increase the ability of students to perform fraction counting operations with cooperative learning of card game techniques? while the purpose of this study was to determine the ability to perform fraction counting operations after the application of cooperative learning in card game techniques. The researcher used Classroom Action Research which was conducted in two cycles or 2 rounds. Each cycle consists of planning, observation, reflection and discussion. The target of the research carried out is MI Ma'arif NU Class V Students Nurul Ulum Bulurejo Benjeng. The data obtained is the result of teacher observation, student activity data, and evaluation test results data. From the results of the analysis it was found that the increase in students' ability to perform fraction counting operations that can be seen from the evaluation test data. Obtaining results in cycle 1 with an average value of 63.6 or 60% completeness in cycle II the average value of students to be 91.44 or reach 92%. The conclusion that can be drawn from this study is that cooperative learning methods can improve